Biomechanical evaluation of ortho-bridge system and proximal femoral nail antirotation in intertrochanteric fractures with lateral wall fracture based on finite element analysis - Long, Yuntao; Liu, Na; Huang, Xiaomeng; Liang, Weiming; Liu, Jianke; Huang, Zhaozhao; Zhang, Yanhui; Wang, Wen (Frontiers in Bioengineering and Biotechnology, 2024)
Background: The integrity of the lateral wall in femoral intertrochanteric fractures significantly impacts fracture stability and internal fixation. In this study, we compared the outcomes of treating intertrochanteric fractures with lateral wall involvement using the orthobridge system (OBS) combined with proximal femoral nail antirotation (PFNA) versus simple PFNA from a biomechanical perspective.Methods: Finite-element models of femoral intertrochanteric fractures with lateral wall involvement were subjected to fixation with OBS combined with PFNA and simple PFNA. Von Mises stress measurements and corresponding displacement assessments for each component of the model, including the proximal femur and lateral wall, were used to evaluate the biomechanical effects of OBS fixation on bone and intramedullary nail stability.Results: Using PFNA alone to fix intertrochanteric fractures with lateral wall involvement resulted in von Mises stress levels on the lateral wall exceeding safe stress tolerances for bone growth. OBS fixation significantly reduced stress on the lateral wall of the femur and minimised the stress on each part of the intramedullary nail, reducing the overall displacement.Conclusions: In cases of intertrochanteric fractures with lateral wall involvement, PFNA fixation alone may compromise the biomechanical integrity of the lateral femoral wall, increasing the risk of postoperative complications. The addition of OBS to PFNA significantly reduces stress on the lateral femoral wall. Consequently, OBS should be considered for lateral wall fixation when managing intertrochanteric fractures combined with lateral wall fractures.